2017
DOI: 10.1111/jphp.12657
|View full text |Cite
|
Sign up to set email alerts
|

The resveratrol derivatives trans-3,5-dimethoxy-4-fluoro-4′-hydroxystilbene and trans-2,4′,5-trihydroxystilbene decrease oxidative stress and prolong lifespan in Caenorhabditis elegans

Abstract: In contrast to resveratrol, the synthetic stilbene derivatives (3) and (6) increase the lifespan of C. elegans, rendering them promising candidates for pharmacological anti-ageing purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 23 publications
4
24
0
Order By: Relevance
“…9d). Our results were consistent with previous studies which reported that resveratrol acts against oxidative stress by regulating cytochromes involved in the metabolism of exogenous substances [41]. Taken together, we speculated that the repair effect of resveratrol on damage due to high sucrose-stearic acid is mainly manifested in two aspects: one is to reduce the oxidative stress of cells and the other is to participate in the metabolism of exogenous substances (Additional files 2, 3, 4, and 5).…”
Section: Resveratrol Protects Sugar and Lipid Damage To Nematodessupporting
confidence: 92%
“…9d). Our results were consistent with previous studies which reported that resveratrol acts against oxidative stress by regulating cytochromes involved in the metabolism of exogenous substances [41]. Taken together, we speculated that the repair effect of resveratrol on damage due to high sucrose-stearic acid is mainly manifested in two aspects: one is to reduce the oxidative stress of cells and the other is to participate in the metabolism of exogenous substances (Additional files 2, 3, 4, and 5).…”
Section: Resveratrol Protects Sugar and Lipid Damage To Nematodessupporting
confidence: 92%
“…KEGG analysis showed that the repair of resveratrol may be related to the metabolism of cytochrome P450 to foreign substances and glutathione metabolism (Fig.4D). Our results were consistent with previous studies which reported that resveratrol acts against oxidative stress by regulating cytochromes involved in the metabolism of exogenous substances (F ischer et al . 2017).…”
Section: Discussionsupporting
confidence: 94%
“…For instance, the garlic-derived thioallyl compounds S-allyl cysteine and S-allylmercaptocysteine have been shown to reduce ROS accumulation and increase C. elegans lifespan [ 17 ]. Similarly, treatment of C. elegans with four synthetic stilbene derivatives extended longevity by reducing ROS accumulation and oxidative stress [ 18 ].…”
Section: The Free Radical Theory Of Aging and Beyondmentioning
confidence: 99%
“…Moreover, respiration inhibition appears to activate the hypoxia-inducible factor-1 (HIF-1) by elevating ROS levels. This activation has been shown to increase longevity [ 17 , 18 ]. Studies in genetically modified mice have shown that a moderately impaired mitochondrial function can result in healthier aging, whereas severely altered mitochondrial homeostasis can be detrimental [ 39 , 40 ].…”
Section: The Free Radical Theory Of Aging and Beyondmentioning
confidence: 99%